(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This research paper introduces a method utilizing the Maclaurin series to analyze the standard Sakiadis problem. The technique uses the Maclaurin series to describe fluid mechanics boundary layers, combining the series solution with diagonal Padé approximants for handling the infinity condition. Additionally, the Hausdorff derivative is used to examine the Sakiadis equation’s fractal formulation. The current approach is consistent with the previous process, and it follows the correct balance. This study is an important resource for furthering research in this area and provides insightful information.